2010
DOI: 10.1007/s11095-010-0299-z
|View full text |Cite
|
Sign up to set email alerts
|

Links Between Cyclosporin Exposure in Tissues and Graft-Versus-Host Disease in Pediatric Bone Marrow Transplantation: Analysis by a PBPK Model

Abstract: Hence, AUC in blood maybe used as an index of cyclosporin efficacy. Using our model, target AUCs in blood could be defined for malignant and non-malignant diseases, as well as the equivalent target values for C(2) and C(0) concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Several investigators have reported cyclosporine AUC in HSCT patients after i.v. administration [3,[10][11][12][13][14][16][17][18][19]26,27]. The method used to calculate or estimate cyclosporine AUC was not described in some of these reports [13], and serum rather than whole blood concentrations (the accepted standard matrix) were reported in another [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have reported cyclosporine AUC in HSCT patients after i.v. administration [3,[10][11][12][13][14][16][17][18][19]26,27]. The method used to calculate or estimate cyclosporine AUC was not described in some of these reports [13], and serum rather than whole blood concentrations (the accepted standard matrix) were reported in another [10].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between cyclosporine AUC after i.v. administration and HSCT outcomes such as aGVHD is just beginning to be explored [11,13,[17][18][19]26,27]. Among these are 2 pediatric studies.…”
Section: Discussionmentioning
confidence: 99%
“…Early post-transplantation exposure to CsA has been related to acute GvHD (aGvHD) severity. [8][9][10] It is now generally agreed that CsA trough blood concentration (TBC) is the pharmacokinetic parameter that best correlates with GvHD outcome. 11,12 Nevertheless, there are no data regarding specific values of CsA TBC to target to favor mild aGvHD without increasing the incidence of severe GvHD.…”
Section: Introductionmentioning
confidence: 99%
“…158 Shortly thereafter, the association of cyclosporine trough concentrations with renal dysfunction 159 and GVHD risk were reported. 160162 TCI of cyclosporine trough concentrations was rapidly adopted and is still used for both cyclosporine and tacrolimus. 161,163 Since then, only TCI of the whole blood trough concentrations of sirolimus has been adopted.…”
Section: Discussionmentioning
confidence: 99%